The investigation of concept mapping as a scaffolding tool in a technologically-mediated, mobile learning, augmented reality environment - Pantela, Nicoletta; Kyza, Eleni A. (My University, 2017)
This study investigated concept maps as a form of support for primary school students' development of conceptual understanding, historical empathy, and for promoting collaborative learning. Students used the same historical learning augmented reality application on a mobile device, worked in pairs, and were divided in two conditions: the experimental group (n=12), supported by a tablet-based concept mapping tool, and the control group (n=11), who only used the learning application on the same mobile devices. The results showed that the experimental group students gained a deeper conceptual understanding after the visit, as evidenced by their concept maps and their discussions during their visit.
Keywords: Computer-supported collaborative learning; Concept maps; Informal learning; Scaffolding